La necrópolis tardorromana de La Molineta, Puerto de Mazarrón (Murcia). Calle Santa Teresa núms. 36-38 - Amante Sánchez, Manuel; García Blázquez, Luis A. (Antigüedad y Cristianismo, 1998)
The Necropolis La Molineta, one of the two that exist in El Puerto de Mazarrón, is situated on a small hill on which was build a large number of small houses, that have been demolished. This has permitted an excavation of various sites where appeared the remains of the Necropolis. This burial place is dated at about the fourth to the sixth centuries when the population of El Puerto de Mazarrón was fairly large. This paper presents an advance of the excavation done on the site, numbers 36 and 38 in the Santa Teresa Street where were dug up twenty graves of different types. The excavation was done during the months of November and December 1988.